Introduction to Bioinformatics - Arthur M Lesk (Oxford University Press, 2002)
Bioinformatics is a scientific discipline and a set of skills that has now become one of the most important information-gathering, data-mining, and knowledge-building tools in current research and clinical applications. Introduction to Bioinformatics is a timely and much-needed textbook which provides an accessible and thorough introduction to a subject which is a fundamental part of biological science today.As a pioneer of the use of bioinformatics techniques in research, Dr Lesk brings experience and expertise to the presentation of this field. The aim of the book is to integrate an understanding of the biological background of bioinformatics with development of necessary computing skills. Without depending on complicated computer science methods or sophisticated programming skills, the book supports and encourages the application of the many powerful computational tools of bioinformatics in a way that is both relevant to and stimulating for the reader.The book contains numerous problems and innovative Weblems (for Web-based problems) to encourage students to engage with the subject and to allow instructors to tune the material to their students' needs.The companion web site for the book provides an interactive link to problems and programs presented in the book, enabling students to develop a hands-on understanding and appreciation of the power of bioinformatics as a research tool.